Pemodelan Peramalan Untuk Meningkatkan Efisiensi Penggunaan Thinner No. 17 Jotun di PT.XYZ - Wardatul Lailiyah; Hafid Syaifullah (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
PT.XYZ is a company engaged in the business of trading industrial and fabricated goods. PT.XYZ often experiences excessive accumulation of thinner which will cause the storage warehouse to pile up. Therefore, this research aims to develop an effective forecasting model in anticipating the use of Thinner No.17 Jotun at Indonesia . The right forecasting method can help companies plan inventory, reduce the risk of overstock or stockout, and increase efficiency in the supply chain. The development of usage from month to month is increasingly uncertain, so the company wants to know how much Thinner expenditure will be used in the following month by referring to the previous month's expenditure using the single moving average, weighted moving average and single exponential smoothing methods. The software used to assist in this research is POM-QM. From the results of research using the Simple Moving Average method, this method has a MAPE value of 5,841%, the forecast size for the next period, namely period 13, is 285 pcs. This shows that the Simple Moving Average method is the most appropriate method to use to solve the problem of using Thinner No.17 Jotun experienced by PT. XYZ because it has the smallest error value. So it can be concluded that the application of this method provides the right solution for the needs of Thinner No.17 Jotun in the next period.